Measurements of serum procollagen-III peptide and M30 do not improve the diagnostic accuracy of transient elastography for the detection of hepatic fibrosis in patients with nonalcoholic fatty liver disease. Issue 6 (June 2015) - Ergelen, Rabia; Akyuz, Umit; Aydin, Yucel; Eren, Fatih; Yilmaz, Yusuf
Abstract : Background: Transient elastography (TE) has recently emerged as an accurate noninvasive imaging method for the diagnosis of liver fibrosis in nonalcoholic fatty liver disease (NAFLD). Here, we tested whether adding serum measures of serum procollagen-III peptide (PIIIP) and caspase-cleaved cytokeratin 18 fragment (M30) to TE could improve its diagnostic accuracy in patients with biopsy-proven NAFLD. Patients and methods: TE was performed in 87 patients with NAFLD. Serum PIIIP and M30 levels were determined by enzyme-linked immunosorbent assay. Liver histology was considered the gold standard. The diagnostic accuracies were assessed by measuring the area under the receiver operating curve. Results: At histopathological examination, 34 patients (39.1%) had significant fibrosis (F2–F4) and 19 patients (21.8%) had advanced fibrosis (F3–F4). Both TE and serum M30 levels were independent predictors of fibrosis, whereas no association was found with PIIIP. No significant differences in terms of sensitivity and specificity for both significant and advanced fibrosis were evident for TE, serum M30, or their combination. Moreover, the area under the receiver operating curves of serum M30 combined with TE did not differ significantly from those of either test alone. Conclusion: Both TE and serum M30 levels are accurate for the noninvasive diagnosis of fibrosis in NAFLD. However, their combination did not improve the overall diagnostic accuracy.